Analysis of Serum Cholesterol, Statins and Atherosclerotic Plaque in Ruptured and Unruptured Intracranial Aneurysm - Pipek, Leonardo Zumerkorn; Rabelo, Nícollas Nunes; Pipek, Henrique Zumerkorn; Telles, Joao Paulo Mota; Barbat, Natalia Camargo; Coelho, Antônio Carlos Samaia da Silva; Yoshikawa, Marcia Harumy; Barbosa, Guilherme Bitencourt; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Intracranial aneurysm (IA) is a major healthcare concern. The use of statin to reduce serum cholesterol has shown evidence to reduce cardiovascular risk in various diseases, but the impact on IA has not been described. This study aims to determine whether statin use, and serum cholesterol levels interfere with outcomes after IA event.Methods A cohort of patients with IA was analyzed. Patients social and demographics data were collected. Modified Rankin scale (mRS) score after 6 months of follow-up was the endpoint. The data regarding statins use, presence or not of atherosclerotic plaque in radiological images and serum cholesterol of 35 patients were included in our study. Linear regression models were used to determine the influence of those 6 variables in the clinical outcome.Results The prevalence of atherosclerotic plaque, high cholesterol and use of statins was 34.3%, 48.5%, and 14.2%, respectively. Statins and serum cholesterol did not impact the overall outcome, measured by mRS after 6 months (p > 0.05), but did show different tendencies when separated by IA rupture status. Serum cholesterol shows an important association with rupture of aneurysm (p = 0.0382). High cholesterol and use of statins show a tendency for worse outcome with ruptured aneurysm, and the opposite is true for unruptured aneurysm. The presence of atherosclerotic plaques was not related with worse outcomes.Conclusions Multiple and opposite mechanisms might be involved in the pathophysiology of IA. Ruptured aneurysms are associated with higher levels of serum cholesterol. Serum cholesterol and statins use were not correlated with worse outcomes, but further studies are important to clarify these relationships.
Keywords: cholesterol; statins; plaques; outcomes for IA